A new species of Forcipomyia Meigen (Diptera: Ceratopogonidae) described with immature stages from India - Paul, Nilotpol; Harsha, Rupa; Mazumdar, Abhijit (Zootaxa, 2014)
Life stages of Forcipomyia parasecuris sp. n. is described, illustrated and photomicrograph based on examination with scanning electron microscope and binocular microscope. The larvae were collected from rotting banana stump of a banana garden at lower Gangetic plain area in India. Absence of ocular sensillum and campaniform sensillum in ocular area of pupa, a synapomorphic character of this proposed new species exhibits its uniqueness in genus Forcipomyia. This is also the first life stage of any Forcipomyia described from India.